Analysis of the Influence of Fitness, Training Consistency, Teamwork, and Mentality on the Performance of Young Athletes - Reni Silviah (Siber International Journal of Sport Education, 2025)
Literature review analysis of the influence of fitness, training consistency, teamwork, and mentality on athlete performance is a scientific article with the aim of analyzing whether athlete performance affects fitness, training consistency, teamwork, and mentality. Qualitative approach method with literature review method to explore and analyze the relationship between fitness, training consistency, teamwork, mentality and athlete performance. The results of this article are: 1) Athlete performance affects fitness, 2) Athlete performance affects training consistency, 3) Athlete performance affects teamwork, 4) Athlete performance affects mentality. Apart from these 4 exogenous variables that affect the endogenous variable of Athlete Performance, there are many other factors including quality of education, discipline, character building, physical activity.